SURFACE, STRUCTURAL AND ELECTRICAL-PROPERTIES OF BATIO3 FILMS GROWN ON P-SI SUBSTRATES BY LOW-PRESSURE METAL-ORGANIC CHEMICAL-VAPOR-DEPOSITION - YOON, YS; YOM, SS; KIM, TW; KIM, HJ; JUNG, M; LEEM, JY; KANG, TW; LEE, SJ (CHAPMAN HALL LTD, 1995)
Metal organic chemical vapour deposition of BaTiO3 using Ba(tmhd)(2), Ti(OC3H(7))(4) and N2O, where tmhd equals 2,2,6,6-tetramethyl-3,5-heptanedionate, via pyrolysis at relatively low temperatures (similar to 370 degrees C) was performed in order to prod uce BaTiO3 insu later gates. Scanning electron microscopy showed that the surfaces of the BaTiO3 films had very smooth morphologies. Atomic force microscopy showed that the BaTiO3 thin film was polycrystalline. X-ray diffraction results indicated that BaTiO3 crystalline films grew on Si(100) with [110] orientation. High resolution transmission electron microscopy measurements showed that the BaTiO3 films were polycrystalline, and an interfacial layer in the BaTiO3/Si interface was formed. The stoichiometry and atomic structure of the BaTiO3 films were investigated by Auger electron spectroscopy and transmission measurements, respectively. Room temperature capacitance-voltage measurements clearly revealed metal-insulator-semiconductor behaviour for samples with BaTiO3 insulator gates, and interface state densities at the BaTiO3/p-Si interface were approximately high, 10(11) eV(-1) cm(-2), at the middle of the Si energy gap.
Keywords: THIN-FILMS; EPITAXIAL-GROWTH; BARIUM-TITANATE; SILICON; OXIDE